The Impact of Coastal Tourism Activities on The Environment and Socio-Culture (Case Study: Berawa Beach, Canggu) - Bella Desita Yusnny; Ni Made Sofia Wijaya; Ni Putu Ratna Sari (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This research aims to analyze the impact of coastal tourism activities on the environment and socio-culture in the Berawa Beach Coastal Area, Canggu. This research uses a qualitative descriptive method with a case study approach. Researcher conducted in-depth interviews with the following sources: Tibubeneng Village, represented by the Head of the Welfare Section, Community Empowerment Institutions, business owners, art shop owners and cafe owners, three local communities and one person who works in the Berawa Coastal Area. This research examines in more depth the impact of coastal tourism activities on the environment and socio-culture. Apart from interviews, researcher made observations and studies from news, articles and journals of previous research. After conducting in-depth interviews with resource people, researche found that there were negative and positive impacts on the environment and socio-culture due to coastal tourism activities in the Berawa Coastal Coastal Area. From the impacts felt by the interviewees, the negative impacts were more significantly felt on the environment due to land conversion and poor waste management. Meanwhile, significant negative socio-cultural impacts are felt, namely the occurrence of traffic jams and crime.